ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA RUMAH SAKIT UMUM DAERAH NAMLEA (Studi Pada RSUD Namlea Kab.Buru Provinsi Maluku) - Siti Ratna Pelupessy; Junaidi Junaidi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine how the waste treatment process is carried out and how environmental cost accounting is applied to a hospital. This research was conducted at the Namlea Regional General Hospital, Kab. Hurry up. This research was conducted using a qualitative approach with a descriptive approach. Data analysis was carried out based on information related to environmental costs, identified environmental costs, prepared a proposed environmental cost report, and analyzed the social responsibility of the Namlea Regional General Hospital. The results of the study indicate that the Namlea Regional General Hospital has carried out waste management properly which can be proven by the absence of internal and external failure costs incurred by the hospital. In relation to the implementation of environmental cost accounting, the hospital has not yet implemented reporting that is specifically related to environmental cost accounting. This is evidenced by the absence of special reports related to environmental costs. Researchers identify, classify, and propose environmental cost reports based on the environmental cost theory developed by Hansen and Mowen. With a special report related to environmental costs, it is hoped that it will facilitate the management of the Namlea Regional General Hospital in making decisions regarding environmental costs and can provide information to stakeholders that the hospital has been responsible for maintaining environmental health.Keywords : Accounting, environmental cost, environmental cost report